The duration of the EC merger control process: Determinants and the impact of the 2004 merger regulation reform - Sven Heim; Kai Hüschelrath; Ulrich Laitenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The duration of merger proceedings held by competition authorities is an important determinant of the efficiency of the entire merger control process. We use a dataset of 2953 Phase I and 92 Phase II investigations completed by the European Commission (EC) between 1999 and 2008 to examine the key determinants of their duration. Differentiating between authority- and caserelated drivers, we find that while the duration of Phase I investigations largely depends on the type of decision and use of simplified procedure, the duration of Phase II investigations is driven by factors such as industry knowledge, the duration of the preceding Phase I investigation, the origin of the notifying firm or the number of identified relevant markets. We also provide evidence that the significant increase in average duration identified after the 2004 merger regulation reform does not imply a decrease in administrative efficiency, as the probability of indepth investigations was correspondingly reduced.
urn:nbn:de:bsz:180-madoc-397426
Keywords: K21; L41; 330; competition policy; ex-post evaluation; merger control; European Union